Classifying breast cancer cell lines of different metastasis potentials using visible resonance raman spectroscopy and machine learning - Wu, Binlin; Zhang, Lin; Jimenez, Kenneth; Boydston-White, Susie; Wang, Eric; Liu, Cheng-hui; Alfano, Robert R. (Conference on lasers and electro-optics, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: Breast cancer cells; Cancer cell lines; Cell culture; Cells; Classification accuracy; Classifieds; Diseases; Machine-learning; Metastatic potential; Principal component analysis; Principal-component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Support vector machines; Support vectors machine; dept.phy

Visible resonance Raman spectroscopic ex vivo studies of mouse brain and organs - Pei, Zhe; Wu, Binlin; Shi, Lingyan; Zhang, Lin; Boydston-White, Susie; Liu, Cheng-Hui; Alfano, Robert R. (Optical Biopsy XX: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2022)
The unique advantage of visible resonance Raman (VRR) spectroscopy using 532 nm excitation wavelength for biological samples is the resonance enhancement of vibrational modes of chemical bonds from cells and tissues. The aim of this study is specifically to reveal the VRR characteristic spectra of different organs in mice, find the molecular alterations in the development of white matter and gray matter of mouse embryos at different ages and study the VRR spectral information of the mouse embryo head using VRR technology.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Amyloid beta and tau protein metabolic changes detected by visible resonance Raman scattering microscopy in Alzheimer's disease mouse model - Shi, Lingyan; Zhou, Yan; Wu, Binlin; Zhu, Ke; Zhang, Shengjia; Boydston-White, Susie; Zhang, Lin; Pei, Zhe; Nguyen, Thien An; Liu, Cheng-Hui; Alfano, Robert R. (Optical Biopsy XXI: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2023)
Alzheimer’s disease (AD) pathogenesis is widely believed to be associated with the production and deposition of the β-amyloid peptide (Aβ) and neurofibrillary tangles (NFTs) which are composed of a highly-phosphorylated form of the microtubule-associated protein tau. Based on the above hypothesis, there are currently no sufficiently effective technologies and drugs for early detection and treatment of AD. Even the most promising new drug Lecanemab that is based on an anti-amyloid monoclonal antibody therapy, has only partially slowed down the cognitive performance of patients with mild impairment caused by Alzheimer's disease. The main symptoms of AD brain tissue lesions in patients are the deposition of β-amyloid peptide and the hyperphosphorylation of tau protein, which aggregates the microtubule structure of neurons. Therefore, Aβ deposition and hyperphosphorylation of Tau are important pathological biomarkers of Alzheimer's disease. Therefore, the main targets of research for AD prevention, detection and pharmaceuticals are still Aβ and Tau protein. The aim of this study was to detect the changes of Aβ and Tau proteins in the mouse brain tissue with AD and control samples using Visible Resonance Raman (VRR) spectroscopic technology. An attempt was made to develop criteria for the detection of early AD lesions by optical spectroscopy technology. The VRR spectra of AD, the control mouse brain tissues, and Aβ and Tau proteins were recorded and analyzed. The AD and the control mouse brain tissue samples were selected from the thalamus, frontal lobe cortex and hippocampus brain areas. VRR technology with high spatial resolution and the resonance-enhanced features of certain protein molecules is first used in this study to detect and characterize the changes of Aβ and Tau proteins in AD mouse brain model. The optical spectroscopy biomarkers of AD and Control brain tissue were identified in fingerprint and the high-wavenumber regions. The Raman spectra of the secondary structure of protein in amide (I-II-III-B-A) are detected and analyzed. The results indicate that the intensity of Amide I decreased at the 1666 cm^-1 corresponding to the β-sheet structure, and the intensity of the amide III bands (1220- 1320 cm^-1) increased in all AD brain tissues. It was also observed that the Raman peaks of 1448 and 980 cm^-1 related to the abundance of proline, serine, and threonine at tau phosphorylation sites were significantly enhanced in the frontal lobe cortex and hippocampus of AD brain tissues. The intensity ratio biomarker of high phosphorylation in the high wavenumber range from 2898 to 2932 cm-1 increased in all AD brain tissues. Changes of protein secondary conformation and abnormally phosphorylated tau or tauopathies were observed. In summary, VRR is a sensitive tool for characterizing protein structural changes and monitoring the tau phosphorylation. It may potentially be used for early detection of AD.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy